Measurement of Serum Free Thyroxine Index May Provide Additional Case Detection Compared to Free Thyroxine in the Diagnosis of Central Hypothyroidism. (8th December 2015) - Pantalone, Kevin M.; Hatipoglu, Betul; Gupta, Manjula K.; Kennedy, Laurence; Hamrahian, Amir H.
Abstract : The diagnosis of central hypothyroidism is often suspected in patients with hypothalamic/pituitary pathology, in the setting of low, normal, or even slightly elevated serum TSH and low free thyroxine (FT4). We present four cases of central hypothyroidism (three had known pituitary pathology) in whom central hypothyroidism was diagnosed after the serum free thyroxine index (FTI) was found to be low. All had normal range serum TSH and free thyroxine levels. This report illustrates that the assessment of the serum FTI may be helpful in making the diagnosis of central hypothyroidism in the appropriate clinical setting and when free T4 is in the low-normal range, particularly in patients with multiple anterior pituitary hormone deficiencies and/or with symptoms suggestive of hypothyroidism.